The improvement of the physical properties of indium tin oxide thin film through annealing processes - Zayer, Mehdi Qasim (2016)
Many optoelectronic devices such as mobile screens, flat panel displays, solar cells and optical storages use Indium Tin Oxide (ITO) due to its ability to retain its good physical properties during the thin film preparation. Therefore, it is of great importance to study the related issues in applications utilizing ITO such as transparency and resistance as well as the underlying cost. These problems can be overcome by the enhanced annealing treatment which is called the Oil Thermal Annealing (OTA) technique in the current work. In this study, ITO thin films of thickness 200 nm are deposited on glass substrates by three preparation techniques, i.e. RF magnetron sputtering, thermal evaporation, and spin coating. The 200 nm ITO thin film is selected due to its relatively lower sheet resistance and higher transparency as compared to those thin films of thicknesses ranging from 100 nm to 300 nm. The RF magnetron sputtering technique is the best candidate in improving the ITO thin film properties. Upon the preparation process, the thin film is treated by OTA, argon and nitrogen operating at temperature range: 150 C < T < 300 C with the annealing time of 2, 6 and 10 min. Measurements and calculations are conducted before and after the preparation and treatment processes. The structural properties and surface morphology of ITO thin films are examined by X-Ray Diffraction (XRD), Atomic Force Microscopy (AFM) and Field Emission Scanning Electron Microscopy (FESEM) before and after the annealing process. The XRD analysis reveals that a polycrystalline structure of maximum diffraction intensity at 2θ = 30.5o and (222) orientation exists in the ITO thin film. FESEM and AFM analyses show that the formation of continuous and homogeneous films are fully covered by pyramidal shaped particles, and roughness value decreases with increasing annealing time. It is also observed that by using OTA treatment, the sheet resistance of ITO thin films prepared by the RF magnetron sputtering technique reduces significantly to 20.8 Ω/sq after 10 min of annealing time. On the other hand, the sheet resistance values of 70.8 Ω/sq and 72.6 Ω/sq are obtained via argon and nitrogen gas treatments, respectively. The As-deposited sheet resistance is 2.8 kΩ/sq. The visible spectrum obtained from the spectrophotometer has shown high transparency values of 95.6 %, 89.9 % and 85 % for RF sputtering which are treated by OTA, argon and nitrogen respectively. OTA gives the highest transparency value, due to the fact that the thermal distribution on the ITO thin film surface treated by OTA is better than those by using argon and nitrogen gases. The OTA treatment process is shown to be successful in improving the ITO thin film properties, which is valuable for many optoelectronic applications. The OTA process can be applied in nano-layers of various sizes and thicknesses at minimum production cost. The total costs incurred after the preparation process (via RF magnetron sputtering technique) and the annealing process (performed at temperature 300 ºC with time 10 min annealing time) using OTA, argon and nitrogen are RM 4.40, RM 46.60 and RM 46.06, respectively. From the current work, it is found that the adhesion strength of the ITO thin film prepared by the RF magnetron sputtering technique and treated by OTA is the highest. Also, the structural, optical and electrical properties can be improved as well by using the proposed technique.